2008
DOI: 10.3733/ca.v064n03p129
|View full text |Cite
|
Sign up to set email alerts
|

A new method is used to evaluate the strategic value of Fresno County farmland

Abstract: Fresno County is a rich agricultural area that faces rapid urbanization and farmland conversion. The county is participating in a strategic, multicounty planning initiative aimed at making sustainable and regionally cohesive land-use decisions. To inform this effort, we conducted a farmland conservation assessment and identified strategic farmlands for prioritization in future conservation efforts. We identified environmental and human predictor variables that affect the viability of existing farmland, used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…These approaches address methodological issues identified in previous comparative approaches based mostly on statistical indicators or local maps [100]. They have been used to develop international comparative approaches of land-use changes [102] and to integrate environmental and human variables in strategic farmland characterization maps [109,111].…”
Section: Integrating Social Data Into Spatial Modelingmentioning
confidence: 99%
“…These approaches address methodological issues identified in previous comparative approaches based mostly on statistical indicators or local maps [100]. They have been used to develop international comparative approaches of land-use changes [102] and to integrate environmental and human variables in strategic farmland characterization maps [109,111].…”
Section: Integrating Social Data Into Spatial Modelingmentioning
confidence: 99%
“…Since 1999, satellite image-based land use change monitoring has been carried out annually. Similar to the Farmland Mapping and Monitoring Program (FMMP) in California, USA, which biennially tracks changes in agricultural and other land uses [110], China's satellite-image based land use monitoring has been implemented annually and was enlarged to cover the whole of mainland China in 2009. As one study indicated, periodic monitoring and inspection is important for compliance and violation reduction [43].…”
Section: The Impact Of Technology Adoption For Land Inspectionmentioning
confidence: 99%
“…The cultivated land site assessment (SA) mainly consists of the assessment of the surrounding, locational, and ecological conditions of the cultivated land in question. The SA system is often based on comprehensive tools and multi-objective methods, such as GIS and remote sensing technology [21][22][23][24]. Through this evaluation model, the SA system is constructed based on different landform types [25].…”
Section: Introductionmentioning
confidence: 99%